Brazilian Water Security Threatened by Climate Change and Human Behavior - André S. Ballarin; José Gescilam Sousa Mota Uchôa; Matheus S. dosSantos; André Almagro; Ianca P. Miranda; Pedro Gustavo C. daSilva; Greicelene J. daSilva; Marcus N. Gomes Júnior; Edson Wendland; Paulo Tarso S. Oliveira (Water Resources Research)
Abstract Water scarcity is a growing concern globally, with climate change and increasing population exacerbating the issue. Here, we introduce a new framework for assessing water availability in 708 Brazilian catchments that considers the effect of CO2 concentrations on potential evapotranspiration, uses CMIP6 bias‐corrected climate change simulations, and presumes an open water balance assumption, while considering the human‐aspect by incorporating water demand projections. We note an average reduction of water security in 81% of the analyzed catchments by 2100. Among these catchments, 37% presented a reduction of future water availability, while 63% undergo a worse scenario due to an increase in human water use, which highlights the role of the human aspect in water security assessment. Our study shows important aspects for both advancing future water availability studies and for drawing a picture of the impacts of changes in climate and water use on Brazilian future water security that may be useful for water resources management practices and advancing hydrologic studies.